Wpływ pokarmu na imagines chrabąszczy Melolontha melolontha i M. hippocastani - Woreta, Danuta; Lipiński, Sławomir; Wolski, Robert (Leśne Prace Badawcze, 2016)
This paper presents the results of studies on the life span, survival, weight and fecundity of the forest cockchafer ( Melolontha hippocastani , Fabricius, 1801) and the common cockchafer ( Melolontha melolontha , Linnaeus, 1758) beetle feeding on Alnus glutinosa (L.) Gaertn., Betula pendula Roth., Carpinus betulus L., Fagus sylvatica L., Larix decidua Mill., Prunus serotina (Ehr.) Borkh., Quercus petraea (Matt.) Liebl., Quercus robur L., Robinia pseudoacacia L., Sambucus nigra L. and Sorbus aucuparia L. em. Hedl. The lifespan and weight of beetles as well as female fertility were examined in 2011 and 2013. Specimen for laboratory tests were collected in the field shortly after leaving their overwintering sites in the soil and identical experimental protocols were applied to both examined species. 576 and 432 beetles were tested in 2011 and 2013, respectively. In 2011, beetles were feeding on A. glutinosa , B. pendula , F. sylvatica , L. decidua Q. petraea leaves and on C. betulus , P. serotina , R. pseudoacacia , S. aucuparia and S. nigra in 2013. Both years, beetles feeding on Q. robur leaves were examined as a control. Our results showed that feeding on leaves of Q. robur and Q. petraea had the largest positive impact on the life time, weight and fecundity of the studied beetles. Leaves of F. sylvatica and L. decidua also constituted an adequate food source for the development of M. melolontha . M. hippocastani , however, did not perform as well when feeding on these two tree species. Females of M. melolontha reared on leaves of B. pendula did not lay eggs. The following plant species had a negative impact on the survival and development of the collected specimen and female fertility: A. glutinosa , S. nigra , P. serotina and R. pseudoacacia . Neither beetle species fed on the leaves of A. glutinosa or S. nigra .